SATS : Northern European Journal of Philosophy (De Gruyter, 2000)
This journal promotes current debates in all philosophical topics, historically and systematically. The aim of SATS is that each paper not only adds to these discussions but helps scholars who are not specialists in the specific fields to understand and assess the content of the debates. Thus each paper is reviewed by an ad hoc international expert on the given subject and by an editorial board member.